2007
DOI: 10.1016/j.bbrc.2007.02.101
|View full text |Cite
|
Sign up to set email alerts
|

Microarray analysis reveals that Type I interferon strongly increases the expression of immune-response related genes in Ubp43 (Usp18) deficient macrophages

Abstract: Type I interferon (IFN) contributes significantly to innate immune responses to pathogen infections in macrophages. Our previous studies demonstrate that Ubp43, an ISG15-specific isopeptidase, is highly expressed in macrophages and noncatalytically inhibits Type I IFN signaling. To understand the effect of Type I IFN and Ubp43 in macrophage activation, we analyzed the expression of IFN-β stimulated genes in wild-type and Ubp43 −/− bone marrow derived macrophages (BMMs). Here, we show that Ubp43 regulates IFN-β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 27 publications
4
30
0
Order By: Relevance
“…Interferoninduced genes were activated in both groups to a similar extent [16]. Furthermore, Zou et al [21] described the activation of genes in interferon-treated macrophages of wild type and Ubp43 mutant mice. Of the 749 genes described in their analysis for the Ubp43 mutant after treatment, 235 were also regulated in our data set.…”
Section: Innate Immune Response Genesmentioning
confidence: 85%
“…Interferoninduced genes were activated in both groups to a similar extent [16]. Furthermore, Zou et al [21] described the activation of genes in interferon-treated macrophages of wild type and Ubp43 mutant mice. Of the 749 genes described in their analysis for the Ubp43 mutant after treatment, 235 were also regulated in our data set.…”
Section: Innate Immune Response Genesmentioning
confidence: 85%
“…mRNA profile studies using cells from USP18/Ubp43 −/− mice indicate that USP18 modulates the expression of many IFN-α-regulated genes (21). To evaluate the effect of USP18 silencing on the transcriptional response to IFN-α, we used a promoter containing repeated ISRE-binding sequences.…”
Section: Resultsmentioning
confidence: 99%
“…We observed previously that the lack of UBP43 results in enhanced and prolonged STAT1 phosphorylation (25) and increased induction of hundreds of ISG (26). More recently, we reported that UBP43 specifically binds to the IFNAR2 subunit and inhibits the activity of receptor-associated JAK1 by blocking the interaction between JAK and IFN receptor (28).…”
Section: Ubp43mentioning
confidence: 87%
“…Importantly, UBP43-deficient cells are hypersensitive to type I IFN and undergo apoptosis upon IFN stimulation (25). Furthermore, lack of UBP43 results in enhanced and prolonged STAT1 phosphorylation and increased induction of hundreds of ISG, as confirmed by gene expression microarray studies (26). Loss of UBP43 in mice results in resistance to the cytopathic effects caused by a number of viruses including lymphocytic choriomeningitis virus (LCMV), vesicular stomatitis virus (VSV), and Sindbis virus (27).…”
Section: H Epatitis B Virus (Hbv)mentioning
confidence: 94%